The 2014, MW6.9 North Aegean earthquake: seismic and geodetic evidence for coseismic slip on persistent asperities - Konca, Ali Ozgun; Cetin, Seda; Karabulut, Hayrullah; Reilinger, Robert; Dogan, Ugur; Ergintav, Semih; Cakir, Ziyadin; Tari, Ergin (OXFORD UNIV PRESS, 2018)
We report that asperities with the highest coseismic slip in the 2014 M(W)6.9 North Aegean earthquake persisted through the interseismic, coseismic and immediate post-seismic periods. We use GPS and seismic data to obtain the source model of the 2014 earthquake, which is located on the western extension of the North Anatolian Fault (NAF). The earthquake ruptured a bilateral, 90 km strike-slip fault with three slip patches: one asperity located west of the hypocentre and two to the east with a rupture duration of 40 s. Relocated pre-earthquake seismicity and aftershocks show that zones with significant coseismic slip were relatively quiet during both the 7 yr of interseismic and the 3-month aftershock periods, while the surrounding regions generated significant seismicity during both the interseismic and post-seismic periods. We interpret the unusually long fault length and source duration, and distribution of pre- and post-main-shock seismicity as evidence for a rupture of asperities that persisted through strain accumulation and coseismic strain release in a partially coupled fault zone. We further suggest that the association of seismicity with fault creep may characterize the adjacent Izmit, Marmara Sea and Saros segments of the NAF. Similar behaviour has been reported for sections of the San Andreas Fault, and some large subduction zones, suggesting that the association of seismicity with creeping fault segments and rapid relocking of asperities may characterize many large earthquake faults.
Keywords: Seismic cycle; Earthquake source observations; Seismicity and tectonics; MARMARA SEA REGION; MOMENT-TENSOR SOLUTIONS; 1999 IZMIT EARTHQUAKE; W 8.3 ILLAPEL; STRONG-MOTION; JOINT INVERSION; SUPERSHEAR RUPTURE; POSTSEISMIC CREEP; ANATOLIAN FAULT; HAYWARD FAULT; Geochemistry & Geophysics